Evaluating Docking Site Local Hematoma Formation and Blood Flow on its Healing Using the Accordion Technique at the End of Tibial Bone Transport - Dong Wang; Shao‐Huang Liu; Guo‐Yu He; Ze Zhang; Juan Li; Ru‐Qi Zhang; Jun‐Jun Shi; Ying‐Wei Jia; Hu‐Yun Qiao; Hong Liu; Bao‐Na Wang; Si‐He Qin; et al. (Orthopaedic Surgery)
Objective At present, due to the lack of early observation methods, the effect of the ‘accordion’ technique on the treatment of nonunion of the docking site varies greatly. In this study, color Doppler ultrasound was used to observe the docking site's local changes and investigate the relationship between local microenvironment changes and bone healing after the accordion technique. Methods 30 patients with tibial bone transport treated at the Department of Orthopedics, Second Hospital of Shanxi Medical University, from May 2018 to June 2022, were analyzed retrospectively. Paired‐sample t‐tests were used for data that conformed to a normal distribution, and paired rank‐sum tests were used for before‐and‐after comparisons that did not conform to a normal distribution. There were 26 males and 4 females, aged 47.3 ± 11.7 years. Before bone transport, the defect gap between tibial bone ends was 6.80 ± 3.61 cm. The steps of the accordion technique were as follows: compression for 7 days, ultrasonic study of the microenvironment at the docking site, distraction for 12 days, latency for 7 days, compression for 14 days, then static fixation and radiological study until complete bone healing. Ultrasound was used to detect the size of the hematoma after 7 days of pressure, and the changes in blood flow before and after the ‘accordion' operation. Results All patients were followed up for 11.9 ± 1.9 months. At the last follow‐up, 22 patients achieved bone healing at the docking site after the treatment of the ‘accordion’ technique. There was a linear negative correlation between the size of the hematoma and the time of bone healing at the docking site (r = −0.639, p < 0.01). According to the Paley healing criteria, 18 of the 22 patients were excellent, and 4 patients were good. Conclusion Hematoma is necessary for the ‘accordion’ technique's success in the treatment of nonunion. The size of the hematoma is negatively related to the time of bone healing. The ‘accordion’ technique can increase the blood flow of tissue around the docking site. Ultrasound can be used to monitor the changes in the microenvironment at the docking site during the ‘accordion’ technique and guide the exact plan and prognosis of the ‘accordion’ technique.